Development of UPS for Pedestrian Traffic Light Using Solar- Piezo and Grid Power Supplies - Mahmud, Muhammad Nizamullah; Baharom, Md Nor Ramdon (Evolution in Electrical and Electronic Engineering, 2022)
Operating the traffic light for pedestrian crossing consume lots of electricity. As non-renewable energy is run out of sources, and the conventional method of generating electricity causes an impact on climate change, the idea of harvesting the energy from environmental sources has become significant. Therefore, this study aims to develop the uninterruptable power supply for the pedestrian crossing using the harvesting method of the solar photovoltaic and piezoelectric transducer. Specifically, it collects the energy from sunlight and vibration at the crossing road and turns it into electricity. In context, the photovoltaic technique converts the photons into electricity when there is enough sunlight while the piezoelectric technique is converting the presence of vibration on the road into electricity. To develop the UPS for the pedestrian traffic lights, the backup supply from the grid is combined. A charge controller for the UPS unit is designed to control the integrated supply of the harvested energy and grid. For the purpose of the store and supplying energy to the battery and load, the charge controller was designed using DC to DC converter which controls by the PWM technique. The simulation result showed a small difference in the output voltage and current of the converter compared to the calculation. The measurement result showed the PV module successfully charge the battery that half in target capacity while the piezoelectric transducer only pushes half of the generated charge into the battery. On that basis, the factor of weather and the mechanical vibration should be considered when determining the sizing of the harvester equipment